On strategy a critical analysis of the Vietnam War - Summers, Harry G. (Presidio Press, 1995)
Summer's inspired analysis of America's war in Vietnam answers the most pressing questions remaining from that terrible conflict more than a decade before Robert McNamara's painful admissions. - See more at: http://www.betterworldbooks.com/on-strategy-id-0891415637.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.NG3mGH95.dpuf